Ethical Leadership as a Strategy in Creating Competitive Advantage in Companies - Salim; Erni Andarwati (Formosa Journal of Sustainable Research, 2023)
In an era of increasingly complex and transparent business, consumers, employees, investors and society in general are increasingly concerned about corporate ethics and social responsibility. Ethical leadership plays an important role in building the trust and reputation of a company, which in turn can bring long-term competitive advantages. This study aims to analyze the role of ethical leadership in creating a company's competitive advantage. Through interviews with a number of informants who are recognized as having strong ethical leadership reputations, this research seeks to explore their views on the importance of ethical leadership and how it can be an effective strategy in achieving competitive advantage. Interview data were analyzed using a qualitative approach and the main findings were categorized to form conclusions